Aerobic fitness is associated with improved repeated sprints ability of basketball players after six weeks of training during preseason - Gantois, P.; Aidar, F. J.; Peixoto Dantas, M.; Medeiros da Silva, L.; Pinheiros Paes, P.; Santana, E. E.; Moreira da Silva Dantas, P.; de Araújo Tinôco Cabral, B. G. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2018)
The repeated sprints ability (RSA) is considered an important attribute for basketball, being aerobic fitness pointed out as limiting factor for repetition of sprints. The aim of the study was to verify if the change in VO2PEAK is related to the improvement of RSA after six weeks of training during preseason. Twelve male college basketball players aged 18-24 participated in the study. Players were submitted to body composition evaluation, maximum incremental treadmill test and RSA test (6x30-m) before and after six weeks of training. For the purpose of the study, the calculation of the change percentage delta was used. Paired t-test was used to verify differences after training and Pearson`s correlation and simple linear regression were used to verify the relationship between Delta%VO2PEAK and Delta%RSA. There were improvements in RSAPEAK (t (1.11) = 2.7, p = 0.023); RSAMEAN (t (1.11)= 2.8, p= 0.019); RSATOTAL (t (1.11)= 2.6, p= 0.028); RSADEC (t (1.11)= 2.9, p = 0.015); and sprints 4 (t (1.11)= 2.4, p= 0.037); 5 (t (1.11)= 3.14, p= 0.010); and 6 (t (1.11)= 3.65, p= 0.004) and VO2PEAK (t (1.11)= -5.4, p <0.001); Delta%VO2PEAK was related to Delta%RSAMEAN (r= -0.667; r2= 0.383), Delta%RSATOTAL (r= -0.673; r2= 0.393), Delta%Sprint 3 (r= -0.669; r2= 0.387), Delta%Sprint 4 (r= -0.659 ; r2 = 0.371), Delta%Sprint 5 (r= -0.689; r2 = 0.413), Delta%Sprint 6 (r= -0.678; r2 = 0.400). It is possible to conclude that ~ 39% of the improvement in variables associated with the maintenance of repeated sprints (RSAMEAN, RSATOTAL, Sprints 3,4,5 and 6) of basketball players was accompanied by an increase of ~ 7.5% in VO2PEAK.